Flower Pollination Algorithm to Tune PID Controller of TCP/AQM Wireless Networks - Eissa, Suad Ali; Shneen, Salam Waley; Ali, Ekbal Hussain (Universitas Muhammadiyah Yogyakarta, 2023)
The current study aims to conduct a simulation that is useful in developing an appropriate design that addresses the problem of congestion in the Internet network through controlling the queue of the router. The simulation is conducted through the proposed model for simulation with different control systems that help in raising the quality of performance such as traditional Proportional Integral Derivative (PID) and advanced optimal by Flower Pollination Algorithm (FPA). It depends for Transmission Control Protocol/ Active Queue Management( TCP/AQM )simulation model for a linear system and another non-linear system. To adjust the network work and raise the level of performance, different control systems were chosen, taking into account all the things that appear through conducting experiments and for different purposes. One of the most important things that must be taken into consideration is the system disturbances as a result of the volume and values of the data, causing congestion . It was shown through the results of the experiments that were conducted considering the cases of the linear and nonlinear system to pass data traffic in the network and by adopting the different techniques of the control units, the preference of optimizasion systems over the traditional ones, as well as the preference of the traditional over without control in close loop, is the improvement of the performance of linear systems compared to the open and closed system without control. The simulation results showed that very clear the superiority of the optimization by FPA-PID controller over the conventional system (PID) , as well as very clear the superiority of the traditional system (PID)over closed system without control and open loop system.